Financial centre primacy around the world: international analysis based on mergers and acquisitions data - Wojcik, D; Keenan, L; Pazitka, V; Urban, M; Wu, W (Oxford University Press, 2023)
We analyse mergers and acquisitions in the financial sector between 2000 and 2017 to explore the domestic hierarchies of financial centres. Across a sample of 16 countries, we reveal different levels of financial centre primacy and explain how these levels change over time. These findings are analysed through a theoretical framework which integrates the literatures on urban primacy, global and world cities and comparative political economy. Situating our findings at the intersection of these literatures allows us to remain sensitive to geography, history and institutions in our analysis of financial centre primacy. Overall, our results show uneven levels of financial centre primacy around the world and that primate financial centres do not universally increase their dominance over time.